Measurement of W-boson polarization in top-quark decay using the full CDF Run II data set - Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; Ashmanskas, W; et al. (2013)
We measure the polarization of W bosons from top-quark (t) decays into final states with a charged lepton and jets, tt̄→W+bW -b̄→ℓνbqq̄′b̄, using the full Run II data set collected by the CDF II detector, corresponding to an integrated luminosity of 8.7 fb-1. A model-independent method simultaneously determines the fraction of longitudinal (f0) and right-handed (f+) W bosons to yield f0=0.726±0. 066(stat)±0.067(syst) and f+=-0.045±0.044(stat) ±0.058(syst) with a correlation coefficient of -0.69. Additional results are presented under various standard model assumptions. No significant discrepancies with the standard model are observed. © 2013 American Physical Society.